Determinação da atividade sérica de adenosina deaminase como método diagnóstico auxiliar da tuberculose bovina - Marcio Roberto Silva (1998)
The detennination of serum levels of adenosine deaminase (ADA), enzyme produced by monocytes/macrophages and lymphocytes, has been used in the diagnosis of human tuberculosis. In the present study, senmi activity of ADA was tested as a complementary test in the diagnosis of bovine tuberculosis. Two hundred fifty-six animals were classified by the comparative skin test using bovine and avian PPDs in reactors (52 animals), from herds where the Mvcobacterium bavis had previously been isolated. and non-reactors (204), from tuberculosis-tree herds. Mean ADA semm values from reactor animals (4.45 +/- 2.33 U/l) were signiiicantly smaller (p=0.008) then those observed in sera from non-reactor animals (6.12 +/-4.47 U/l). When non-reactor animals from a herd with clinical cases of bovine enzootic leukosis were withdrawn from analysis, the mean ADA serum values of the non-reactor group (5.12 +/- 3.75 U/1) was not different from that of the reactor group (p=0.28). Using two different cut0H points, 6.12 U/l and 15 U/l, there was no agreement between the determination of ADA serum values and the comparative skin test in the detection of tuberculous animals (kappa = -0.086 and kappa = -0.082, respectively). In conclusion, the determination of ADA serum activity was not a good complementary test for bovine tuberculosis, because it was not possible to distinguish skin test reactors and non-reactors by ADA serum levels.